2022
DOI: 10.3390/polym14091758
|View full text |Cite
|
Sign up to set email alerts
|

Panel Products Made of Oil Palm Trunk: A Review of Potency, Environmental Aspect, and Comparison with Wood-Based Composites

Abstract: Oil palm plantations have expanded rapidly in Southeast Asia, particularly in Indonesia and Malaysia. A lot of products, including food and other edible products, oleo-chemicals, cosmetics, personal and household care, pharmaceutical products, and biodiesels are derived from palm oil, thus making them one of the most economically important plants. After 25–30 years of age, the palms are felled and replaced due to declining oil production. Oil palm trunks (OPT) are considered significant waste products. The tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Oil palm trunk is frequently used as a raw material in the manufacture of composite materials such as laminated veneer lumber (LVL); plywood, flooring, furniture, and other composites [9][10][11][12][13][14][15]. However, it was reported that oil palm wood extracted from the trunk has four major drawbacks, i.e., low mechanical strength, inferior dimensional instability, poor durability, and poor machining characteristics [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Oil palm trunk is frequently used as a raw material in the manufacture of composite materials such as laminated veneer lumber (LVL); plywood, flooring, furniture, and other composites [9][10][11][12][13][14][15]. However, it was reported that oil palm wood extracted from the trunk has four major drawbacks, i.e., low mechanical strength, inferior dimensional instability, poor durability, and poor machining characteristics [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The global production of palm oil reached 410.7 million ton in 2019 which occupied about 28.3 million hectares of plantation land area [12]. Indonesia, Malaysia, and Thailand contributed about 88% of the global production as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia, Malaysia, and Thailand contributed about 88% of the global production as shown in Figure 1. However, the increase in production capacity of oil palm in the past decade only increased by 15.6% in Malaysia unlike the other countries where it doubled in Thailand and increased by nearly 3 folds in Indonesia [12]. Oil palm industry contributes to the majority (about 85%) of biomass waste in Malaysia, 10% for Municipal Solid Waste (MSW) and 5% for other biomass resources [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This causes environmental problems for the new palm generation or air pollution due to fire. Therefore, the comprehensive review conducted by Nuryawan et al [55] summarizes the utilization of OPT into products made of oil palm fibers mainly derived from OPT, and its application for the substitution of wood panel products. Some research works have also analyzed oil palm fibers derived from OPT for the exploitation of their potential as raw material to process into various conventional composite panel products, such as plywood and laminated board, particleboard, or binderless and cement board.…”
mentioning
confidence: 99%